KAJIAN KUALITAS AIR SUNGAI CIPINANG BAGIAN HILIR DITINJAU DARI PARAMETER BOD DAN DO MENGGUNAKAN MODEL QUAL2E - Damarany, Purnisa; Fachrul, Melati Ferianita; Astono, Widyo (Jurnal Teknologi Lingkungan Universitas Trisakti, 2009)
Assesment water quality of the downstream Cipinang river using QUAL2E model (BOD and DO as parameter). QUAL2E is a water quality modeling which able to simulate water quality’s changing in Cipinang river with BOD and DO discharging in this river. Analytical research is carried out in the downstream Cipinang river, which starts from Halim to the meet point of Cipinang river and Sunter river in Cipinang Bawah. The scenario in this research is done to know Cipinang river’s water quality after the adding of waste debit to reach 3 and 6 with BOD concentration’s about 162.73 mg/L and 161.23 mg/L while the results of fields sampling as the first condition. This river is divided to 7 reaches and into small parts as an element. The result of hydraulics simulation shows that debit, velocity and depth of this river are in statistical condition, except in reach 3 and 6. The simulation water quality’s result shows that BOD’s curve down with the cumulative of river’s distant. It’s just going up in reach 3 and 6 while DO concentration is in the fluctuation way. This model uses hydraulic calibration, BOD and DO constant calibration, and water quality calibration using BOD and DO as parameter with 3 comparison which are field sampling’s result, streeter-phelps model and QUAL2E simulation output. BOD and DO concentration have been far from the decision of Governor Jakarta No.582 year 1995 and it makes the ecosystem decreasing. The strategies to solve this problem that can be done for example make the velocity become 1.2 m/s, river depth become 0.5 m, up the DO concentration about 80%, down the BOD concentration in reach 1, 3 and 6 about 96.34%, 96,31% and 96,71% using communal WWTP, monitoring drainage systems that entering into this river and make waterfall as the aeration for coming up the DO.